Technology in language teaching: Trends, approaches, and implementations (Insights from TEwT from 2016 to 2020) - Teuku Zulfikar; Emawati; Cut Fadhilah Alfa Karim (Universitas Islam Negeri Ar-Raniry, 2026)
The domain of language instruction has attracted sustained scholarly attention over the past decade, with a marked increase in research dedicated to technology-mediated language learning. This article presents a systematic review of empirical articles published in Teaching English with Technology (TEwT), a journal that has consistently featured studies on diverse technological applications in English language teaching. A retrospective analysis was conducted on 140 articles published in TEwT between 2016 and 2020. The primary objective was to identify and categorize the types of technologies or media employed in language instruction and to examine their influence on instructional processes. The findings reveal that the majority of articles comprise empirical studies that systematically investigate the effects of technological interventions on language acquisition processes. Through content analysis and systematic data coding, several patterns of technological adoption and implementation in language education were identified. The results confirm the increasing inevitability and progression of technology integration in language instruction, characterized by growing diversity in the types of technologies utilized and the emergence of novel instructional alternatives. Consequently, language educators now have access to an expanding array of technological resources. Furthermore, the accessibility of technology-mediated instruction has improved significantly, as contemporary educators and students demonstrate enhanced competency in utilizing these tools. However, the efficacy of diverse technological and media applications in language education remains context-dependent, as the outcomes of technology-mediated instruction are substantially influenced by the specific pedagogical, institutional, and sociocultural contexts in which they are implemented.